2013
DOI: 10.1017/s1751731113000232
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of lameness and claw lesions during different stages in thereproductive cycle of sows and the impact on reproduction results

Abstract: Lameness in sows is an emerging disease condition with major effects on animal welfare and economics. Yet the direct impact on reproduction results remains unclear. The present field study investigated the impact of lameness and claw lesions throughout the reproductive cycle on (re)production results of sows. In five farms, a total of 491 group-housed sows were followed up for a period of one reproductive cycle. Sows were assessed for lameness every time they were moved to another area in the farm. Claw lesion… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
68
0
1

Year Published

2014
2014
2021
2021

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 67 publications
(84 citation statements)
references
References 24 publications
6
68
0
1
Order By: Relevance
“…The fact, that shoulder lesions are a major problem in farrowing crates becomes clear from the present study as well as the study of Bonde et al (2004), who even found a prevalence of 20% in farrowing crates. There is evidence that lesions that occur at different points of the production cycle have negative impacts on the reproductive performance, and thus longevity, of the sows (Pluym et al, 2013). If lesions that are caused by crate fixtures could be minimized by loose-lactating, benefits might outweigh the additional management efforts during periods of loose-housing.…”
Section: Integument Lesionsmentioning
confidence: 99%
“…The fact, that shoulder lesions are a major problem in farrowing crates becomes clear from the present study as well as the study of Bonde et al (2004), who even found a prevalence of 20% in farrowing crates. There is evidence that lesions that occur at different points of the production cycle have negative impacts on the reproductive performance, and thus longevity, of the sows (Pluym et al, 2013). If lesions that are caused by crate fixtures could be minimized by loose-lactating, benefits might outweigh the additional management efforts during periods of loose-housing.…”
Section: Integument Lesionsmentioning
confidence: 99%
“…In 23.33% of dry sows severe problems in locomotion were presented (score 1 and 2). In a couple of papers of Pluym et al (2011Pluym et al ( , 2013) data on the average prevalence of lameness about 10% or below this value are provided, but it can reach up to 28%.…”
Section: Resultsmentioning
confidence: 99%
“…Previous studies reported the association of heel lesions and wall cracks with decreased litter weight, increased pre-weaning piglet mortality and higher odds of stillborn piglets (Fitzgerald et al 2012;Pluym et al 2013). Our results indicate that combinations of lesions on the dorsal and ventral part of the claws, negatively affected the reproduction parameters considered.…”
Section: Discussionmentioning
confidence: 98%
“…Lameness is an animal-based welfare indicator (Welfare Quality ® consortium 2009) which reduces the productivity of a pig herd by reducing sow longevity and the number of pigs produced per sow per year due to increased involuntary culling rates of sows (Anil et al 2005;Engblom et al 2008). Some claw lesions were also associated with decreased litter weight, increased pre-weaning piglet mortality and higher odds of stillborn and crushed piglets (Fitzgerald et al 2012;Pluym et al 2013).…”
mentioning
confidence: 99%